2015
DOI: 10.1016/j.apsusc.2015.07.025
|View full text |Cite
|
Sign up to set email alerts
|

The surface modifications of multi-walled carbon nanotubes for multi-walled carbon nanotube/poly(ether ether ketone) composites

Abstract: Please cite this article as: Z. Cao, L. Qiu, Y. Yang, Y. Chen, X. Liu, The surface modifications of multi-walled carbon nanotubes for multi-walled carbon nanotube/poly (ether ether ketone) composites, Applied Surface Science (2015), http://dx.Abstract The effects of surface modifications of multi-walled carbon nanotubes (MWCNTs) on the morphology, dynamic mechanical and tribological properties of multi-walled carbon nanotube/poly (ether ether ketone) (MWCNT/PEEK) composites have been investigated. MWCNTs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…However, tribo‐materials exhibit different tribological performances in different operating conditions. To study the tribological properties of the PEEK composites in different working conditions, we performed two model experiments: pin‐on‐disc and block‐on‐ring. A schematic of the UMT‐2 tribometer is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, tribo‐materials exhibit different tribological performances in different operating conditions. To study the tribological properties of the PEEK composites in different working conditions, we performed two model experiments: pin‐on‐disc and block‐on‐ring. A schematic of the UMT‐2 tribometer is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, an ideal tribo‐material is expected to have a lower coefficient of friction and wear rate. Based on observations, the incorporation of appropriate fillers is an effective method to decrease the coefficient of friction and improve the wear resistance of PEEK resins …”
Section: Introductionmentioning
confidence: 99%
“…These oxidative treatments usually result in shortening of the CNTs' length and formation of surface reactive groups, such as hydroxyl, carbonyl, and mainly Carboxyl. Furthermore, the inorganic impurities of the Al-Fe catalyst used in the preparation of CNTs are solubilized by the acids and the concentration of the impurities is gradually decreased with treatment time [20,23,26,27]. It has been shown that acid functionalized CNTs has good dispersibility in water and organic solvents, and the carboxylic functional groups give a stronger nanotube-polymer interaction, leading to enhanced values in mechanical properties of the CNTs/polymer composite [27,28].…”
Section: Acid Treatmentmentioning
confidence: 99%
“…As a high‐performance semi‐crystalline thermoplastic polymer, poly‐ether‐ether‐ketone (PEEK) has outstanding mechanical properties, chemical inertness, and good thermal stability over a wide temperature range, which makes it widely used as a replacement for metal components in many applications such as the bearing materials, bone implants, and piston rings . However, it is difficult to use PEEK in pristine form because of its high friction coefficient and stick‐slip behavior . In order to solve these problems, many researchers have focused on the tribological property improvements of the PEEK by adding a variety of fillers such as SiO 2 , Al 2 O 3 , carbon fibers (CF), graphene, PTFE, carbon nanotubes etc., as well as their various combinations .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to use PEEK in pristine form because of its high friction coefficient and stick‐slip behavior . In order to solve these problems, many researchers have focused on the tribological property improvements of the PEEK by adding a variety of fillers such as SiO 2 , Al 2 O 3 , carbon fibers (CF), graphene, PTFE, carbon nanotubes etc., as well as their various combinations . Among these various lubricating fillers, CFs and PTFE particles have been widely used because of their excellent properties.…”
Section: Introductionmentioning
confidence: 99%